SISTEM INFORMASI INVENTORY BARANG BERBASIS WEB DENGAN MENGGUNAKAN METODE WATERFALL PADA PT. MUSASHI AUTO PARTS INDONESIA - Yoga Religia; Heriyanto2 Heriyanto2 (Teknik Informatika, Universitas Pelita Bangsa, 2019)
Information systems are systems that process and provide information for decision making in an organization. Inventory information system is a system used to process and provide information about inventory data in a company for decision making. Goods Inventory Information System at PT. MUSASHI AUTO PARTS INDONESIA still uses manual processes. The purpose of this study is to develop an ongoing inventory information system at PT. MUSASHI AUTO PARTS INDONESIA to support web-based warehouse inventory control. The methodelogy used to develop this inventory information system is the waterfall method and uses the PHP and MySQL programming languages. Inventory information systems can overcome problems related to the quality of information and the clarity of information produced. Admin as user of inventory information system concludes that this system can facilitate the processing, searching, and reporting of data in and out of warehouse goods. Keywords: Information Systems, Inventory, Waterfall, PHP, MYSQL.